2021
DOI: 10.1167/iovs.62.3.37
|View full text |Cite
|
Sign up to set email alerts
|

CSF1/CSF1R-mediated Crosstalk Between Choroidal Vascular Endothelial Cells and Macrophages Promotes Choroidal Neovascularization

Abstract: Purpose This study examined the role of the CSF1/CSF1Raxis in the crosstalk between choroidal vascular endothelial cells (CVECs) and macrophages during the formation of choroidal neovascularization (CNV). Methods Quantitative reverse transcriptase (QRT)-PCR, Western blot and ELISA measured the production and release of CSF1 from human choroidal vascular endothelial cells (HCVECs) under hypoxic conditions. Western blot detected CSF1 released from HCVECs under hypoxic con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Conversely, another study ( Zhu et al, 2018 ) with different glucose concentrations showed that up-regulating FOXO1 can prevent HLECs from oxidative damage induced by high glucose via beta-casomorphin-7 treatment. FOXO1 is also associated with choroidal neovascularization, and retina vein occlusions have also been reported ( Chen et al, 2019 ; Zhou et al, 2021b ). However, there is a lack of research on the role of up-regulated FOXO1 in ARC pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, another study ( Zhu et al, 2018 ) with different glucose concentrations showed that up-regulating FOXO1 can prevent HLECs from oxidative damage induced by high glucose via beta-casomorphin-7 treatment. FOXO1 is also associated with choroidal neovascularization, and retina vein occlusions have also been reported ( Chen et al, 2019 ; Zhou et al, 2021b ). However, there is a lack of research on the role of up-regulated FOXO1 in ARC pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacologic Flt3 inhibitor AC220 is specific at nanomolar levels, but the authors used 0.1–10 mg/ml (0.18–18 mM). At 6 orders of magnitude above specificity, AC220 has many off target effects including inhibition of platelet-derived growth factor receptors and colony stimulating factor 1 (Csf1) receptor 16 , which both can stimulate choroidal angiogenesis 17 19 . In addition, experiments in this prior publication were performed at 4–8 weeks of age, but the sex and genetic background of the Flt3 −/− mice were not reported.…”
Section: Discussionmentioning
confidence: 99%
“…However, Flt3 −/− mice can exhibit an enhanced response to Csf1, leading to DC development 20 . Since Csf1 expression increases after laser injury 19 , Csf1-dependent signaling is a possible compensatory mechanism for DC maturation in Flt3 −/− mice, explaining why Flt3 −/− mice have increased DCs after laser injury.…”
Section: Discussionmentioning
confidence: 99%
“…CSF1-neutralizing antibodies increase the expression of the M1-type macrophage marker but decreased the expression of the M2-type marker. Moreover, CSF1/CSF1R also ameliorates laser-induced CNV formation in mice [ 78 ]. CSF1 released from HCVECs under hypoxic conditions is important for inducing macrophage M2 polarization and CNV formation.…”
Section: Macrophages In Cnvmentioning
confidence: 99%